A Genome-Wide Association Study of Field and Seedling Response to Individual Stem Rust Pathogen Races Reveals Combinations of Race-Specific Genes in North American Spring Wheat - Edae, Erena A.; Pumphrey, Michael O.; Rouse, Matthew N. (Frontiers in Plant Science, 2018)
Stem rust of wheat caused by the fungal pathogen Puccinia graminis f. sp. tritici historically caused major yield losses of wheat worldwide. To understand the genetic basis of stem rust resistance in contemporary North American spring wheat, genome-wide association analysis (GWAS) was conducted on an association mapping panel comprised of 250 elite lines. The lines were evaluated in separate nurseries each inoculated with a different P. graminis f. sp. tritici race for three years (2013, 2015 and 2016) at Rosemount, Minnesota allowing the evaluation of race-specificity separate from the effect of environment. The lines were also challenged with the same four races at the seedling stage in a greenhouse facility at the USDA-ARS Cereal Disease Laboratory. A total of 22,310 high-quality SNPs obtained from the Infinium 90,000 SNPs chip were used to perform association analysis. We observed often negative and sometimes weak correlations between responses to different races that highlighted the abundance of race-specific resistance and the inability to predict the response of the lines across races. Markers strongly associated with resistance to the four races at seedling and field environments were identified. At the seedling stage, the most significant marker-trait associations were detected in the regions of known major genes (Sr6, Sr7a and Sr9b) except for race QFCSC where a strong association was detected on chromosome arm 1AL. We postulated the presence of Sr2, Sr6, Sr7a, Sr8a, Sr9b, Sr11, Sr12, Sr24, Sr25, Sr31, and Sr57 (Lr34) in this germplasm based on phenotypic and marker data. We found that combinations of genes conferring resistance to specific P. graminis f. sp. tritici races accounts for the prevalent stem rust resistance in North American spring wheat.